Sistem Pengolahan Data Simpan Pinjam Pada KPRI-GR-Rambah Kabupaten Rokan Hulu - Elyandri Prasiwiningrum; Torkis Nasution (RJOCS (Riau Journal of Computer Science), 2015)
Cooperative is an important organization in promoting economic growth. By becoming one of the alternatives for people to improve their quality of life and develop the business through the savings and loan services, therefore it is necessary to repair a computerized data processing system sothat the savings and loan transaction process can be better managed, effective and efficient. Existing data is then processed using Microsoft Visual Basic 2010 by using a MySQL database, with this system will further improve the performance of cooperatives and promote cooperative itself